Deepening the understanding of redundancy procedures in a COVID-19 context: The Spanish case - Clemente-Almendros, José Antonio; Boldeanu, Florin Teodor; Drumea, Cristina; Ajour El Zein, Samer (Akademiai Kiado Zrt., 2024)
This paper investigates the use of redundancy procedures (RPs) by small and medium-sized enterprises (SMEs) in Spain during the COVID-19 pandemic. The novelty of this study is that it goes beyond the direct influence of the determinants of RPs on RP use, and analyses how the interactions among them moderate the direct effect. In contexts of rising uncertainty, businesses need to adapt their operations and fixed costs, including staffing. While teleworking is an alternative to RPs, our results show that it was not enough to deal with the negative impact of a worsening crisis. Moreover, when the survival of the business is at stake, the use of RPs increases further when the company is simultaneously affected by changes in demand and liquidity issues. We argue that our results reveal the need for flexible tools along with the policies that take into account the fact that businesses' reactions are contingent on their exposure to risk.